Pengaruh Penggunaan Model Polya Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas V SD N 05 Sungai Aur - Al Hidayat, Muhammad; Rossa, Rona; Hendriyani, Maifit; Adriantoni; Wulandari, Suci (Samsara Institute Publisher, 2025)
This study investigated the effect of Polya’s problem-solving model on the mathematical problem-solving ability of elementary school students. A quasi-experimental research method with a posttest-only design was employed, involving fifth-grade students of SD N 05 Sungai Aur. The experimental group was taught using Polya’s model, while the control group received conventional instruction. Data analysis included normality and homogeneity tests, which confirmed that the data were normally distributed (Sig = 0.132 for the experimental group and 0.118 for the control group) and homogeneous (Sig = 0.520). Descriptive analysis showed that the experimental group had a higher mean score (86.9) compared to the control group (82.8). However, the independent sample t-test produced a significance value of 0.182 (p > 0.05), indicating no significant difference between the two groups. The findings suggest that the use of Polya’s model did not have a significant effect on improving students’ mathematical problem-solving ability.